2022
DOI: 10.1021/acscatal.2c01423
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Pd-Catalyzed Efficient Synthesis of Imidazolones via Dehydrogenative Condensation between Ureas and 1,2-Diols

Abstract: A heterogeneously catalyzed protocol for the acceptorless dehydrogenative condensation between N,N′-disubstituted ureas and 1,2-diols to afford imidazolones was developed. Palladium nanoaggregates stabilized onto an alumina matrix with suitable acidic properties, namely, [Pd/Al 2 O 3 ], was designed and successfully applied as efficient and reusable heterogeneous nanocatalyst for this relevant transformation. The methodology developed showed its wide applicability through the synthesis of more than 25 imidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…Efforts of Arango-Daza et al led to the successful synthesis of imidazol-2-ones (119) using the reactants N,N′disubstituted urea (117) and 3,4-dihydroxy-1-butene or 1aryl-1,2-ethanediols (118) in the presence of PdNPs [Pd/Al 2 O 3 ] (Scheme 33) at 150 °C for 24 h in dibutyl ether in 41-87% yields. 86 Among the studied MNPs on different supports, PdNPs over -Al 2 O 3 were found to afford excellent catalytic efficiency and structural properties. These MNPs were prepared from -Al 2 O 3 and K 2 PdCl 4 , and characterisation of the catalyst was undertaken with the aid of XRD, HR-TEM, STEM, EDX, Raman spectroscopy, XPS, and BET.…”
Section: Scheme 31 Pdnps Promoted N-arylation Published By Yamada And...mentioning
confidence: 92%
“…Efforts of Arango-Daza et al led to the successful synthesis of imidazol-2-ones (119) using the reactants N,N′disubstituted urea (117) and 3,4-dihydroxy-1-butene or 1aryl-1,2-ethanediols (118) in the presence of PdNPs [Pd/Al 2 O 3 ] (Scheme 33) at 150 °C for 24 h in dibutyl ether in 41-87% yields. 86 Among the studied MNPs on different supports, PdNPs over -Al 2 O 3 were found to afford excellent catalytic efficiency and structural properties. These MNPs were prepared from -Al 2 O 3 and K 2 PdCl 4 , and characterisation of the catalyst was undertaken with the aid of XRD, HR-TEM, STEM, EDX, Raman spectroscopy, XPS, and BET.…”
Section: Scheme 31 Pdnps Promoted N-arylation Published By Yamada And...mentioning
confidence: 92%
“…23 Cabrero-Antonino, Adam et al reported the synthesis of a variety of imidazolones through the acceptorless dehydrogenative condensation of ureas and diols. 24 This reaction was catalyzed by the combination of Pd/Al 2 O 3 and ZnO, able to mediate the diol dehydrogenation. Moreover, the catalytic mixture proved to be reusable in two catalytic cycles.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In this perspective, acceptorless dehydrogenative coupling (ADC) of alcohols provides a sustainable and economic pathway using several homogeneous and heterogeneous catalytic systems. 4,[16][17][18][19][20][21] Noticeable advances in the ADC between alcohols and nitriles using homogeneous catalysts of 4d and 5d metals (Ru, Ir and Os) have been observed; 4,[22][23][24] however, reports on the use of heterogeneous catalysts in these reactions are scanty. 4 Presently, there is a quest for replacing these expensive noble metal catalysts with the cost-effective, environment-friendly and earth-abundant 3d transition metal catalysts.…”
Section: Introductionmentioning
confidence: 99%